Analyzing Gender and Cultural Disparities in Science Literacy and Numeracy: Socioeconomic, Linguistic, and Educational Perspectives - Egi Adha Juniawan; Dwi Yulianto (Journal of Innovation in Educational and Cultural Research, 2026)
The current research examines differences between genders and cultures concerning scientific literacy and numeracy skills of Indonesian secondary school students residing in Sundaland, Indonesia. This quantitative study used hierarchical linear modeling (HLM) and analyzed results from literacy tests, questionnaires, and interviews conducted among the stratified sample. According to the analysis, Javanese students achieved the best results in the test; Balinese respondents scored the lowest due to unequal infrastructure and limited access to technology. Moreover, males showed greater results in numeracy, whereas females demonstrated their advantage in scientific literacy. In addition, the use of the mother tongue helped students achieve a better understanding of the concepts; Batak and Minangkabau respondents with long-standing cultural learning traditions showed higher results. Thus, this paper supports the idea that inclusive educational policy is a key factor for closing the literacy gap in ethnically diverse countries. Ethnomathematics and multicultural education practices should be used more often for improving academic performance in Indonesia. Even though this work has some limitations, including the geographic location of respondents and the lack of longitudinal studies, the author managed to conduct a valuable study on the issue under consideration. It will contribute to the development across diverse populations.